Role of E-selectin in bleomycin induced lung fibrosis in mice. Issue 2 (1st February 2000) - Azuma, Arata; Takahashi, Satoru; Nose, Masato; Araki, Kimi; Araki, Masatake; Takahashi, Takuo; Hirose, Mayumi; Kawashima, Hiroto; Miyasaka, Masayuki; Kudoh, Shoji
Abstract : BACKGROUND: Bleomycin (BLM), a well known anti-cancer drug, often causes acute lung injury and fibrosis by mechanisms that are not well understood. It is suspected that some proteases and active oxygen species generated from inflammatory cells cause the lung injury and subsequent lung fibrosis. It was therefore hypothesised that inhibition of adhesion of inflammatory cells to the endothelium might prevent these developments. METHODS: BLM (100 mg/kg) was injected into the tail veins of ICR mice to evaluate the induction of E-selectin, an adhesion molecule known to induce neutrophil attachment on endothelial cells. E-selectin mRNA induction was detected by reverse transcriptase polymerase chain reaction (RT-PCR). The myeloperoxidase (MPO) activities in the lung tissues of BLM treated and control mice were compared to evaluate neutrophil infiltration. Pathological changes in the lungs of soluble E-selectin transgenic mice (TG) and their TG negative (non-TG) littermates after BLM treatment were also compared. Serum samples of TG mice and non-TG mice were tested for their ability to block the binding of sialyl Lewis x to recombinant E-selectin in vitro. RESULTS: E-selectin mRNA was maximally induced at six hours after BLM treatment in the ICR mice. The soluble form of E-selectin which can competitively inhibit the binding of sialylated antigens on inflammatory cells to E- and P-selectins on the endothelium was detected in the serum of TG mice. BLM induced lung fibrosis occurred in non-TG mice but not in TG mice. This result confirms the finding that the serum of TG mice inhibits the binding of sialyl Lewis x to E-selectin in vitro. CONCLUSION: E-selectin plays an essential role in BLM induced lung fibrosis through the induction of neutrophil and other inflammatory cell accumulation, and soluble E-selectin may be of use in the prophylactic treatment of lung fibrosis.